"Und es gab keinen Antwortenden". Einseitige direkte Rede in biblischen Erzählungen - Susanne Gillmayr-Bucher (Protokolle zur Bibel, 2016)
A chararacteristic of biblical narrative is the high amount of direct speech. The narrating voice is accompanied by different voices which are engaged in lifely dialogues or present their ideas and reflections in a monologic way. This article focuses on monologic speech and simple unresolved dialogues. Analysing examples from the book of Judges the various occurrences are classified according to their function in the narration.